PENGARUH AROMATERAPI INHALASI LAVENDER TERHADAP KECEMASAN PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS - Sarah ' Anastasia; Bayhakki ' '; Fathra Annis Nauli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract This study aimed to explore the effect of lavender aromatheraphy inhalation on the anxiety of chronic renal failure patients undergoing hemodialysis. This study used “Quasy experimental design” with “non equaivalent control-group” design. This study was conducted at RSUD Arifin Achmad Riau Province on 30 patients. 15 patients as the experiment group and 15 patients as the control group based on purposive sampling technique. The instrument used was zung self-rating anxiety Scale questionnaire which had been tested for validity and reliability. Lavender aromatheraphy inhalation was given to the experiment group once for 5 minutes. The analyses used are univariate analysis such as normality, homogenity and frequency test. The bivariate analysis used t-dependent and t- independent test. The result of study showed p value of 0,000 (<0,05) which mean that there was an anxiety difference between experiment group and control group with anxiety decrease of 4,33 on the experiment group and increase of 0,86 on the control group. This result indicates that the anxiety score of experiment group is lower than the control group after the lavender aromatheraphy inhalation was given. The study result expects that lavender aromatheraphy inhalation can be used as one of the nursing intervention to lower the anxiety of chronic renal failure patients undergoing hemodialysis.